A Series Resonant Converter-Based Multichannel LED Driver With Inherent Current Balancing and Dimming Capability - Gucin, Taha Nurettin; Fincan, Bekir; Biberoglu, Muhammet (Institute of Electrical and Electronics Engineers (IEEE), 2019)
This study proposes a high-efficiency light-emitting-diode (LED) driver based on the series resonant converter (SRC) topology. As the major requirement from LED driver circuits is the ability of providing constant current for maintaining a certain luminescence level, it is utilized that the SRC operates as a frequency-controlled constant current source when the switching frequency is lower than half of the resonance frequency. This approach ensures a reliable and dimmable constant current power supply that can operate in an open-loop configuration. A design procedure for the proposed multichannel LED driver is given and experimental results for a prototype that is capable of delivering 50 V–0.35 A output for six channels are presented. It is also shown that the proposed driver is capable of ensuring high efficiency values (92%–93.5%) for a wide output power (14–58 W).